Changes in occupational demand structure and their impact on individual wages - Alexandra Fedorets (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
This paper estimates wage losses arising due to changes in the structure of demand for occupations. The data on occupational changes made for the sake of adjustment to the changes in the demand structure come from the German reunification of 1990. Endogenous occupational changes are instrumented by the post-reunification demand properties of the occupation of the apprenticeship completed in the GDR. The IV computation reveals a negative wage effect of nearly 35 log points in 1991/92. This effect is persistent over time: after almost 10 years after reunification the negative wage effect associated with occupational changes due to the relocation of individual human capital across occupations is more than 20 log points.
Keywords: J24; J62; I21; P21; 330; human capital; wage premium; occupational change; natural experiment; Lohnstruktur; Arbeitsnachfrage; Beruf; Arbeitsmobilität; Systemtransformation; Neue Bundesländer